Experimental trace element partition coefficients for upper mantle pyroxenites coexisting with H2O with CO2, NaCl and NH3 fluids - Matthew J. M. Phillips; Svyatoslav S. Shcheka; Stephen F. Foley (Contributions to Mineralogy and Petrology, 2026)
Experimental determinations of trace element distribution between rocks/minerals and fluids at mantle pressures and temperatures have concentrated on eclogite and on fluids containing H 2 O with or without the addition of NaCl. Here we present data for websterite (pyroxenite) coexisting with five different fluids: H 2 O, H 2 O+CO 2 , H 2 O+NaCl, H 2 O+CO 2 +NaCl and H 2 O+NH 3 . All experiments were conducted at 1.5 GPa and 800˚C using glassy carbon fluid traps that were kept in a frozen state following experiments until trace elements in the fluid traps were analysed by laser cryoablation-ICP-MS. Results show that Rb, Ba, Sr, Pb and Li are fluid-mobile, with lower rock/fluid partition coefficients (D Rock/Fluid ) for all mixed fluids relative to pure H 2 O. Lowest values (0.0004–0.123) are found for H 2 O+NH 3 fluids. Almost all for the REE are 2 O+CO 2 +NaCl and H 2 O+NH 3 fluids, as are the HFSE, which also show lower D Rock/Fluid than for eclogites, with or without NaCl. Re and Pt are fluid-mobile, with D Re Pt and lowest values for both in H 2 O+CO 2 fluids. The first row transition elements show D-values ranging from 0.0004 to 2.88 with only 4 of 35 data points > 1. D Rock/Fluid increase in the order Cu Rock/Fluid ,particularly low-Al clinpyroxenes.

Radiological characterisation and inter-laboratory comparison of naturally occurring radioactive materials (NORM) in building materials used in Ireland - R.E. Djabou; M. Dodek; C. Sainz; I. Fuente; L. León Vintró; O. Hanley; J. Goggins; M. Foley (Science of The Total Environment, 2026)

Genomic insights into the evolutionary history and cryptic diversity of two-toed sloths (Choloepus) in Amazonia - Larissa S. Arantes; Luísa S. Marins; Linda Hagberg; Radarane Santos Sena; Benoit de Thoisy; Marta Svartman; Mariluce Rezende Messias; Cláudia R. Silva; Nicole M. Foley; William J. Murphy; Camila C. Ribas; Fabrício R. Santos; et al. (Molecular Phylogenetics and Evolution, 2026)

Gamma emissions from NORM in building materials: A position paper on national transposition of the Euratom basic safety standard - M. Dodek; R.E. Djabou; C. Sainz; I. Fuente; L.L. Vintró; O. Hanley; J. Goggins; M. Foley (Journal of Environmental Radioactivity, 2026)

Associations between monthly fine particulate matter and ozone exposure, and postneonatal infant mortality in the United States, 2005–2017 - Sanjida J. Mowla; Alison K. Krajewski; Adrien A. Wilkie; Kristen Foley; Kristen M. Rappazzo; Thomas J. Luben (Science of The Total Environment, 2026)

Matched case-control study of air pollution and infant mortality in North Carolina - Thomas J. Luben; Alison K. Krajewski; Adrien A. Wilkie; Kristen Foley; Kristen M. Rappazzo (Environmental Research, 2026)

Early Pliocene (Zanclean) sea surface temperature for PlioMIP3 - Harry J. Dowsett; Kevin M. Foley (Global and Planetary Change, 2026)

Drought Reduces Formation, but Enhances Persistence, of Mineral‐Associated Organic Matter in a Grassland Soil - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Nicole DiDonato; Katerina Estera‐Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; William Kew; Ljiljana Paša‐Tolić; Eric Slessarev; Jennifer Pett‐Ridge (Global Change Biology, 2026)
Drought effects are pervasive in terrestrial ecosystems, yet there is limited understanding of how drought impacts the transformation of plant carbon (C) inputs to mineral‐associated organic matter (MAOM)—the largest and slowest‐cycling pool of soil organic carbon (SOC). In a 12‐week 13 C‐CO 2 greenhouse labeling experiment, we tracked the formation of MAOM derived from the two dominant sources of plant C input to the mineral soil—living root inputs ( 13 C‐rhizodeposits) and decaying root inputs ( 13 C‐root detritus)—under normal moisture and droughted conditions in a semiarid grassland soil. At the end of the 12‐week period, we also measured the persistence of 13 C‐MAOM formed from rhizodeposits versus root detritus via a subsequent persistence assay. Drought reduced the formation of MAOM derived from living roots by decreasing rhizodeposits, reducing microbial growth rates, and altering the composition of organic matter, lipids, and metabolites. Drought initially delayed the formation of MAOM derived from root detritus by slowing the early stages of root litter decomposition (week 4–8), but did not decrease total MAOM formation by the end of the 12‐week period. Notably, drought enhanced the persistence of MAOM derived from root detritus, but did not influence the persistence of MAOM derived from rhizodeposits. Our results provide some of the first direct evidence that drought can reduce the formation of MAOM in a grassland soil, but may enhance its persistence, based on the source of plant input from which MAOM is derived.

Pier pressure: 23 years of incidental sea turtle captures at recreational fishing piers along Florida’s Gulf coastline - Robby J. Brannum; Karrie Minch; Morgan Wideroff; Meghan E. Koperski; Colin P. Shea; Allen M. Foley; Robbin N. Trindell (Frontiers in Marine Science, 2025)
Incidental captures of sea turtles during fishing activities affect their populations worldwide. Previous research has documented the impacts of commercial fisheries in nearshore and offshore waters, and research-based minimization measures are now required to reduce sea turtle take. However, incidental captures of juvenile-to-adult sea turtles also occur in recreational fisheries in nearshore and inshore waters, although the magnitude and distribution of these events are poorly understood. We analyzed Florida Sea Turtle Stranding and Salvage Network (STSSN) reports between 2000 and 2022 to identify sea turtles incidentally captured by recreational anglers from fishing piers along Florida’s Gulf coastline. We used a negative binomial regression model to quantify temporal and spatial changes in the mean number of pier-captured sea turtles reported at Gulf piers over the 23-year study period. There were 452 documented incidents of loggerheads ( Caretta caretta ), green turtles ( Chelonia mydas ), and Kemp’s ridleys ( Lepidochelys kempii ) hooked at 33 different piers. Juvenile and subadult turtles of all three species were pier-captured as well as adult loggerhead and Kemp’s ridley turtles. The number of turtles for each of the three species captured varied over time, but overall the number of reported captures increased regionally over the 23-year study. Most turtles captured and recovered at recreational fishing piers were successfully rehabilitated and released back to the wild (84.7.%). The observed increases in sea turtle pier capture reports likely reflect some combination of increased turtle numbers in the nearshore environment, increased use of piers as foraging habitat, and increased reporting requirements and effort. This analysis offers insights into the complex interactions between sea turtles and pier-based recreational fishing in the Gulf and could help inform conservation efforts while supporting responsible recreational fishing practices.

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Recombination-aware phylogenomics - Frank T. Burbrink; Dylan DeBaun; Nicole M. Foley; William J. Murphy (Trends in Ecology & Evolution, 2025)

Regional differentiation in somatic growth and maturation attributes for loggerhead sea turtles (Caretta caretta) in the Northwest Atlantic - Larisa Avens; Margaret M. Lamont; Allen M. Foley; Benjamin M. Higgins; Lyndsey N. Howell; Gretchen Lovewell; Donna J. Shaver; Brian A. Stacy; J. Shelby Walker; Jamie M. Clark; Amy A. Wallace; Hannah B. Vander Zanden (Marine Biology, 2025)

Overwintering humpback whales adapt foraging strategies to shallow water environments at the mouth of the Chesapeake Bay, Virginia, USA - Jeanne M. Shearer; Heather J. Foley; Zachary T. Swaim; Vincent M. Janik; Andrew J. Read (Marine Mammal Science, 2025)
Some humpback whales from the Northwestern Atlantic population forgo migration to the Caribbean, spending winter months feeding along the U.S. mid‐Atlantic coast. We studied the foraging behavior of these whales at the mouth of the Chesapeake Bay, Virginia during winter from 2017 to 2022. While shipping channels here reach depths of up to 30 m, most of the area is 11–15 m deep. This shallow‐water environment poses physical constraints on classical humpback whale feeding modes. We deployed 20 digital acoustic tags (DTAGs) on humpback whales and identified foraging lunges from accelerometer data, detecting 788 lunges from 10 animals. Tagged whales averaged a single lunge per dive, lunging primarily in a horizontal orientation, with limited maneuvering compared to other study sites. Our results indicate that some elements of humpback whale foraging behavior are conserved across environments, but that the shallow depths in our study area constrain how animals are able to feed. The relatively high lunge rates we observed suggest this area is an important foraging ground. However, foraging in shipping channels increases the risk of ship strikes, which frequently occur in this area.

Organophosphate ester flame retardant chemicals and maternal depression during pregnancy - Ixel Hernandez-Castro; Sandrah P. Eckel; Caitlin G. Howe; Max T. Aung; Kurunthachalam Kannan; Morgan Robinson; Helen B. Foley; Tingyu Yang; Mario J. Vigil; Xinci Chen; Brendan Grubbs; Laila Al-Marayati; et al. (Environmental Research, 2024)

Linking Vegetation Characteristics of Madagascar’s Spiny Forest to Habitat Occupancy of Lepilemur petteri - Yedidya R. Ratovonamana; Celina Apel; Davidson H. Hajanantenaina; William J. Foley; Daniel Kübler; Stella Nevermann; S. Jacques Rakotondranary; Eleanor M. Stalenberg; Jörg U. Ganzhorn (International Journal of Primatology, 2024)
Climatic changes with unpredictable weather conditions have negative effects on many primates. With several lemur species reaching their ecological limits in the dry and hypervariable spiny forest, Madagascar might provide an example for understanding adaptations of primates to unpredictable conditions. Here, we aimed to identify vegetation characteristics that allow Lepilemur petteri to persist in an environment at the limit of its ecological niche. For this, we linked the patchy distribution of the species to vegetation characteristics described on the ground and by remote sensing reflecting primary production (Enhanced Vegetation Index from MODIS) for 17 sites in nine regions, spread over 100 km along Tsimanampetsotse NP. We verified the results on a smaller scale by radio-tracking and vegetation analyses related to home ranges of 13 L. petteri . Remote sensing indicated that L. petteri is more likely to occur in forests where the variation of the annual primary production and the interannual variability of the month with the lowest primary production are low. Lepilemur petteri was more likely to occur with increasing densities of large trees, large food tree species (diameter ≥ 10 cm) and octopus trees ( Alluaudia procera ). Alluaudia procera provide food year-round and shelter in the spiny forest where large trees with holes are absent. High tree species diversity might buffer food availability against failure of certain tree species to produce food. These findings illustrate limiting constraints of climatic hypervariability for lemurs and indicate benefits of forest restoration with high numbers of tree species for biodiversity conservation.

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Long-term ambient sulfur dioxide exposure during gestation and preterm birth in North Carolina, 2003–2015 - Adrien A. Wilkie; Thomas J. Luben; Kristen M. Rappazzo; Kristen M. Foley; Courtney G. Woods; Marc L. Serre; David B. Richardson; Julie L. Daniels (Atmospheric Environment, 2024)

Song fragments recorded on a tagged juvenile humpback whale ( Megaptera novaeangliae ) on a winter feeding ground at the mouth of the Chesapeake Bay, Virginia, USA - Dana L. Adcock; Jeanne M. Shearer; Heather J. Foley; Zach T. Swaim; Andrew J. Read (Marine Mammal Science, 2024)

The path from root input to mineral-associated soil carbon is dictated by habitat-specific microbial traits and soil moisture - Noah W. Sokol; Megan M. Foley; Steven J. Blazewicz; Amrita Bhattacharyya; Nicole DiDonato; Katerina Estera-Molina; Mary Firestone; Alex Greenlon; Bruce A. Hungate; Jeffrey Kimbrel; Jose Liquet; Marissa Lafler; et al. (Soil Biology and Biochemistry, 2024)

Prenatal exposures to organophosphate ester metabolites and early motor development in the MADRES cohort - Ixel Hernandez-Castro; Sandrah P. Eckel; Xinci Chen; Tingyu Yang; Mario J. Vigil; Helen B. Foley; Kurunthachalam Kannan; Morgan Robinson; Brendan Grubbs; Deborah Lerner; Nathana Lurvey; Laila Al-Marayati; et al. (Environmental Pollution, 2024)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Active populations and growth of soil microorganisms are framed by mean annual precipitation in three California annual grasslands - Megan M. Foley; Steven J. Blazewicz; Karis J. McFarlane; Alex Greenlon; Michaela Hayer; Jeffrey A. Kimbrel; Benjamin J. Koch; Victoria L. Monsaint-Queeney; Keith Morrison; Ember Morrissey; Bruce A. Hungate; Jennifer Pett-Ridge (Soil Biology and Biochemistry, 2023)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Adult male Cuvier's beaked whales ( Ziphius cavirostris ) engage in prolonged bouts of synchronous diving - William R. Cioffi; Nicola J. Quick; Heather J. Foley; Danielle M. Waples; Zachary T. Swaim; Jeanne M. Shearer; Daniel L. Webster; Ari S. Friedlaender; Brandon L. Southall; Robin W. Baird; Douglas P. Nowacek; Andrew J. Read (Marine Mammal Science, 2021)
Studies of the social behavior of Cuvier's beaked whales ( Ziphius cavirostris ) are challenging because of their deep‐water habitat usually far from shore and the limited time they spend at the surface. The sociality of these deepest diving mammals is of interest, however, especially for our understanding of how social systems evolve in extreme habitats. High levels of scarring suggest that males compete agonistically for access to females and so we predicted that associations among adult males would be unstable due to competitive exclusion. We tested this prediction by evaluating the diving behavior of animals within social groups off Cape Hatteras, North Carolina, considering diving synchrony a proxy for group membership. Using data from satellite‐linked depth‐recording tags, we found that adult male–male pairs showed extended periods of synchrony in diving behavior, while all pairs that included an adult male with an individual of another age and/or sex dove synchronously for less than a day. We assessed three hypotheses to explain these surprising results: sexual segregation; extended bouts of male–male competition; and the presence of male alliances. Finally, we considered testable predictions to distinguish among these explanations.

Deconstructing Protein in the Diet and Biomass of Colobine Primates - Katarina D. Evans; William J. Foley; Colin A. Chapman; Jessica M. Rothman (International Journal of Primatology, 2021)

Drivers of longitudinal telomere dynamics in a long‐lived bat species, Myotis myotis - Nicole M. Foley; Eric J. Petit; Thomas Brazier; John A. Finarelli; Graham M. Hughes; Frédéric Touzalin; Sébastien J. Puechmaille; Emma C. Teeling (Molecular Ecology, 2020)
Age‐related telomere shortening is considered a hallmark of the ageing process. However, a recent cross‐sectional ageing study of relative telomere length (rTL) in bats failed to detect a relationship between rTL and age in the long‐lived genus Myotis ( M. myotis and M. bechsteinii ), suggesting some other factors are responsible for driving telomere dynamics in these species. Here, we test if longitudinal rTL data show signatures of age‐associated telomere attrition in M. myotis and differentiate which intrinsic or extrinsic factors are likely to drive telomere length dynamics. Using quantitative polymerase chain reaction, rTL was measured in 504 samples from a marked population, from Brittany, France, captured between 2013 and 2016. These represent 174 individuals with an age range of 0 to 7+ years. We find no significant relationship between rTL and age ( p = .762), but demonstrate that within‐individual rTL is highly variable from year to year. To investigate the heritability of rTL, a population pedigree ( n = 1744) was constructed from genotype data generated from a 16‐microsatellite multiplex, designed from an initial, low‐coverage, Illumina genome for M. myotis . Heritability was estimated in a Bayesian, mixed model framework, and showed that little of the observed variance in rTL is heritable ( h 2 = 0.01–0.06). Rather, correlations of first differences, correlating yearly changes in telomere length and weather variables, demonstrate that, during the spring transition, average temperature, minimum temperature, rainfall and windspeed correlate with changes in longitudinal telomere dynamics. As such, rTL may represent a useful biomarker to quantify the physiological impact of various environmental stressors in bats.

Correcting for within-season demographic turnover to estimate the island-wide population of King Penguins (Aptenodytes patagonicus) on South Georgia - C. M. Foley; W. F. Fagan; H. J. Lynch (Polar Biology, 2020)

Trans-Tasman Cumulative Effects Management: A Comparative Study - Kathryn K. Davies; Karen T. Fisher; Gemma Couzens; Andrew Allison; Elizabeth Ingrid van Putten; Jeffrey M. Dambacher; Melissa Foley; Carolyn J. Lundquist (Frontiers in Marine Science, 2020)

A method to estimate pre‐exploitation population size - Catherine M. Foley; Heather J. Lynch (Conservation Biology, 2020)
Antarctic fur seals ( Arctocephalus gazella ) were commercially exploited on the subantarctic island of South Georgia for over 100 years and nearly driven to extinction. Since the cessation of harvesting, however, their populations have rebounded, and they are now often considered a nuisance species whose impact on the terrestrial landscape should be mitigated. Any evaluation of their current population requires the context provided by their historic, pre‐exploitation abundance, lest ecologists fall prey to shifting baseline syndrome in which their perspective on current abundance is compared only with an altered state resulting from past anthropogenic disturbance. Estimating pre‐exploitation abundance is critical to defining species recovery and setting recovery targets, both of which are needed for the International Union for the Conservation of Nature's recent efforts to develop a green list of recovering species. To address this issue, we reconstructed the South Georgia fur seal harvest from 1786 to 1908 from ship logbooks and other historical records and interpolated missing harvest data as necessary with a generalized linear model fit to the historical record. Using an approximate Bayesian computation framework, harvest data, and a stochastic age‐structured population model, we estimated the pre‐exploitation abundance of Antarctic fur seals on South Georgia was 2.5 million females (95% CI 1.5–3.5 million). This estimate is similar to recent abundance estimates, and suggests current populations, and the ecological consequences of so many fur seals on the island, may be similar to conditions prior to human harvest. Although the historic archive on the fur sealing era is unavoidably patchy, the use of archival records is essential for reconstructing the past and, correspondingly, to understanding the present. Article impact statement : Defining species recovery requires an understanding of baseline population state, which can be estimated through statistical methods.

Microbial assemblages reflect environmental heterogeneity in alpine streams - Scott Hotaling; Mary E. Foley; Lydia H. Zeglin; Debra S. Finn; Lusha M. Tronstad; J. Joseph Giersch; Clint C. Muhlfeld; David W. Weisrock (Global Change Biology, 2019)
Alpine streams are dynamic habitats harboring substantial biodiversity across small spatial extents. The diversity of alpine stream biota is largely reflective of environmental heterogeneity stemming from varying hydrological sources. Globally, alpine stream diversity is under threat as meltwater sources recede and stream conditions become increasingly homogeneous. Much attention has been devoted to macroinvertebrate diversity in alpine headwaters, yet to fully understand the breadth of climate change threats, a more thorough accounting of microbial diversity is needed. We characterized microbial diversity (specifically Bacteria and Archaea) of 13 streams in two disjunct Rocky Mountain subranges through 16S rRNA gene sequencing. Our study encompassed the spectrum of alpine stream sources (glaciers, snowfields, subterranean ice, and groundwater) and three microhabitats (ice, biofilms, and streamwater). We observed no difference in regional (γ) diversity between subranges but substantial differences in diversity among (β) stream types and microhabitats. Within‐stream (α) diversity was highest in groundwater‐fed springs, lowest in glacier‐fed streams, and positively correlated with water temperature for both streamwater and biofilm assemblages. We identified an underappreciated alpine stream type—the icy seep—that are fed by subterranean ice, exhibit cold temperatures (summer mean

Heard but not seen: Occurrence of Kogia spp. along the western North Atlantic shelf break - Lynne E. W. Hodge; Simone Baumann‐Pickering; John A. Hildebrand; Joel T. Bell; Erin W. Cummings; Heather J. Foley; Ryan J. McAlarney; William A. McLellan; D. Ann Pabst; Zachary T. Swaim; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2018)

King Penguin populations increase on South Georgia but explanations remain elusive - C. M. Foley; T. Hart; H. J. Lynch (Polar Biology, 2018)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

The Kraken in the Aquarium: Questions that Urgently Need to be Addressed in Order to Advance Marine Conservation - John A. Cigliano; Amy Bauer; Megan M. Draheim; Melissa M. Foley; Carolyn J. Lundquist; Julie-Beth McCarthy; Katheryn W. Patterson; Andrew J. Wright; E. C. M. Parsons (Frontiers in Marine Science, 2016)

Sexual Health Concerns Among Cancer Survivors: Testing a Novel Information-Need Measure Among Breast and Prostate Cancer Patients - Sheila A. Crowley; Sallie M. Foley; Daniela Wittmann; Christina H. Jagielski; Rodney L. Dunn; Patricia M. Clark; Jennifer J. Griggs; Catherine Peterson; Marcia Leonard; Lawrence C. An; John T. Wei; James E. Montie; et al. (Journal of Cancer Education, 2016)

Genetics and mapping of a novel downy mildew resistance gene, Pl 18 , introgressed from wild Helianthus argophyllus into cultivated sunflower (Helianthus annuus L.) - L. L. Qi; M. E. Foley; X. W. Cai; T. J. Gulya (Theoretical and Applied Genetics, 2016)

Soil‐Hydrological Responses to Rainfall Variation in a Subtropical Australian Landscape - S. Kodur; J. B. Robinson; J. L. Foley; D. M. Silburn (Irrigation and Drainage, 2015)
Reliable water supply for farming is a global concern, including the Lockyer Valley region, Australia. Knowledge of rainfall variation and resulting irrigation demand and deep drainage can improve crop water use and minimize salinity. Therefore, we modelled irrigation demand and deep drainage for different land‐use types of the Lockyer Valley and classified them according to rainfall. During the periods of extremely low rainfall (mean = 468 mm yr ‐1 ), deep drainage fell by 35–239 mm yr ‐1 , whereas irrigation demand rose by 160–310 mm yr ‐1 , relative to extremely high rainfall (1138 mm yr ‐1 ). With all land‐use types, deep drainage rose with water input, but it was consistent in the order (mean, mm yr ‐1 ): lucerne (8–11), native grass (13), sorghum–wheat sequence (37–64), bare fallow (169) and sweetcorn–broccoli–bean sequence (225). Decadal trends in irrigation demand and deep drainage signalled a raising future irrigation demand; and in turn potential deep drainage risks if irrigation is not managed wisely. These findings will have broader implications for crop and environment management under rainfall variation. Copyright © 2015 John Wiley & Sons, Ltd.

Rapid water quality change in the E lwha R iver estuary complex during dam removal - Melissa M. Foley; Jeffrey J. Duda; Matthew M. Beirne; Rebecca Paradis; Andrew Ritchie; Jonathan A. Warrick (Limnology and Oceanography, 2015)
Dam removal in the United States is increasing as a result of structural concerns, sedimentation of reservoirs, and declining riverine ecosystem conditions. The removal of the 32 m Elwha and 64 m Glines Canyon dams from the Elwha River in Washington, U.S.A., was the largest dam removal project in North American history. During the 3 yr of dam removal—from September 2011 to August 2014—more than ten million cubic meters of sediment was eroded from the former reservoirs, transported downstream, and deposited throughout the lower river, river delta, and nearshore waters of the Strait of Juan de Fuca. Water quality data collected in the estuary complex at the mouth of the Elwha River document how conditions in the estuary changed as a result of sediment deposition over the 3 yr the dams were removed. Rapid and large‐scale changes in estuary conditions—including salinity, depth, and turbidity—occurred 1 yr into the dam removal process. Tidal propagation into the estuary ceased following a large sediment deposition event that began in October 2013, resulting in decreased salinity, and increased depth and turbidity in the estuary complex. These changes have persisted in the system through dam removal, significantly altering the structure and functioning of the Elwha River estuary ecosystem.

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

Four species of arboreal folivore show differential tolerance to a secondary metabolite - Lora M. Jensen; Ian R. Wallis; Karen J. Marsh; Ben D. Moore; Natasha L. Wiggins; William J. Foley (Oecologia, 2014)

Climate change response in Europe: what’s the reality? Analysis of adaptation and mitigation plans from 200 urban areas in 11 countries - D. Reckien; J. Flacke; R. J. Dawson; O. Heidrich; M. Olazabal; A. Foley; J. J.-P. Hamann; H. Orru; M. Salvia; S. De Gregorio Hurtado; D. Geneletti; F. Pietrapertosa (Climatic Change, 2014)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

A Pharm-Ecological Perspective of Terrestrial and Aquatic Plant-Herbivore Interactions - Jennifer Sorensen Forbey; M. Denise Dearing; Elisabeth M. Gross; Colin M. Orians; Erik E. Sotka; William J. Foley (Journal of Chemical Ecology, 2013)

Sex hormones differentially influence voluntary running activity, food intake and body weight in aging female and male rats - J. Andries Ferreira; Andrea M. Foley; Marybeth Brown (European Journal of Applied Physiology, 2012)

Nest-site selection and nest depredation of semi-aquatic turtles on golf courses - Shawna M. Foley; Steven J. Price; Michael E. Dorcas (Urban Ecosystems, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

A rehabilitation exercise program to remediate skeletal muscle atrophy in an estrogen-deficient organism may be ineffective - Marybeth Brown; J. Andries Ferreira; Andrea M. Foley; Kaitlyn M. Hemmann (European Journal of Applied Physiology, 2012)

Palatability mapping: a koala's eye view of spatial variation in habitat quality - Ben D. Moore; Ivan R. Lawler; Ian R. Wallis; Colin M. Beale; William J. Foley (Ecology, 2010)
Ecologists trying to understand the value of habitat to animals must first describe the value of resources contained in the habitat to animals and, second, they must describe spatial variation in resource quality at a resolution relevant to individual animal foraging. We addressed these issues in a study of koalas ( Phascolarctos cinereus ) in a Eucalyptus woodland. We measured beneficial and deterrent chemical characteristics as well as the palatability of trees using a near‐infrared spectroscopic model based on direct feeding experiments. Tree use by koalas was influenced by tree size and foliar quality but was also context‐dependent: trees were more likely to be visited if they were surrounded by small, unpalatable trees or by large, palatable trees. Spatial autocorrelation analysis and several mapping approaches demonstrated that foliar quality is spatially structured in the woodland at a scale relevant to foraging decisions by koalas and that the spatial structure is an important component of habitat quality.

A Metabolomic Approach to Identifying Chemical Mediators of Mammal–Plant Interactions - David J. Tucker; Ian Robert Wallis; Jessica M. Bolton; Karen J. Marsh; Adam A. Rosser; Ian M. Brereton; Dean Nicolle; William J. Foley (Journal of Chemical Ecology, 2010)

Nutritional Ecology of Ateles chamek in lowland Bolivia: How Macronutrient Balancing Influences Food Choices - Annika M. Felton; Adam Felton; Jeff T. Wood; William J. Foley; David Raubenheimer; Ian R. Wallis; David B. Lindenmayer (International Journal of Primatology, 2009)

Methyl jasmonate does not induce changes in Eucalyptus grandis leaves that alter the effect of constitutive defences on larvae of a specialist herbivore - M. L. Henery; I. R. Wallis; C. Stone; W. J. Foley (Oecologia, 2008)

Effects of poaching on bull mating success in a free ranging African elephant (Loxodonta africana) population in Tarangire National Park, Tanzania - D. R. S. Ishengoma; A. M. Shedlock; C. A. H. Foley; L. J. Foley; S. K. Wasser; S. T. Balthazary; B. M. Mutayoba (Conservation Genetics, 2008)

Seasonal patterns in biomass smoke pollution and the mid 20th‐century transition from Aboriginal to European fire management in northern Australia - David M. J. S. Bowman; Joanne K. Dingle; Fay H. Johnston; David Parry; Michael Foley (Global Ecology and Biogeography, 2007)
Aim Globally, most landscape burning occurs in the tropical savanna biome, where fire is a characteristic of the annual dry season. In northern Australia there is uncertainty about how the frequency and timing of dry season fires have changed in the transition from Aboriginal to European fire management. Location In the tropical eucalypt savannas that surround the city of Darwin in the northwest of the Northern Territory of Australia. Methods Our study had three parts: (1) we developed a predictive statistical model of mean mass (µg) of particulates 10 µm or less per cubic metre of air (PM 10 ) using visibility and other meteorological data in Darwin during the dry seasons of 2000 and 2004; (2) we tested the model and its application to the broader air shed by (a) matching the prediction of this model to PM 10 measurements made in Darwin in 2005, (b) matching the predictions to independent measurements at two locations 20 km to the north and south of Darwin and (c) matching peaks in PM 10 to known major fire events in the region (2000–01 dry seasons); and (3) we used the model to explore changes in air quality over the last 50 years, a period that spans the transition from Aboriginal to European land management. Results We demonstrated that visibility data can be used reliably as a proxy for biomass burning across the largely uncleared tropical savannas inland of Darwin. Validations using independent measurements demonstrated that our predictive model was robust, and geographically and temporally representative of the regional airshed. We used the model to hindcast and found that seasonal air quality has changed since 1955, with a trend to increasing PM 10 concentrations in the early dry season. Main conclusions The results suggest that the transition from Aboriginal to European land management has been associated with an increase in fire activity in the early months of the dry season.

Seasonal patterns in biomass smoke pollution and the mid 20th-century transition from Aboriginal to European fire management in northern Australia - David M. J. S. Bowman; Joanne K. Dingle; Fay H. Johnston; David Parry; Michael Foley (Global Ecology and Biogeography, 2006)

MRI evaluation of topical heat and static stretching as therapeutic modalities for the treatment of eccentric exercise-induced muscle damage - R. C. Jayaraman; R. W. Reid; J. M. Foley; B. M. Prior; G. A. Dudley; K. W. Weingand; R. A. Meyer (European Journal of Applied Physiology, 2004)

Comparison of the climate simulated by the CCM3 coupled to two different land-surface models - Delire C.; Levis S.; Bonan G.; Foley J.; Coe M.; Vavrus S. (Climate Dynamics, 2002)

Coping with chemical complexity in mammal-plant interactions: near-infrared spectroscopy as a predictor of Eucalyptus foliar nutrients and of the feeding rates of folivorous marsupials - Allen M. McIlwee; Ivan R. Lawler; Steven J. Cork; William J. Foley (Oecologia, 2001)

Measurements and Modeling of Carbon and Nitrogen Cycling in Agroecosystems of Southern Wisconsin: Potential for SOC Sequestration during the Next 50 Years - Christopher J. Kucharik; Kristofor R. Brye; John M. Norman; Jonathan A. Foley; Stith T. Gower; Larry G. Bundy (Ecosystems, 2001)

Cation partitioning versus temperature in spinel: optimization of site occupants - J. A. Foley; S. E. Wright; J. M. Hughes (Physics and Chemistry of Minerals, 2001)

Relationship Between Chemical Functional Groups on Eucalyptus Secondary Metabolites and their Effectiveness as Marsupial Antifeedants - Ivan R. Lawler; Bart; M. Eschler; Darren M. Schliebs; William J. Foley (Journal of Chemical Ecology, 1999)

Ecological Example of Conditioned Flavor Aversion in Plant–Herbivore Interactions: Effect of Terpenes of Eucalyptus Leaves on Feeding by Common Ringtail and Brushtail Possums - Ivan R. Lawler; Jessica Stapley; William J. Foley; Bart M. Eschler (Journal of Chemical Ecology, 1999)

Administration of a 5HT 3 receptor antagonist increases the intake of diets containing Eucalyptus secondary metabolites by marsupials - I. R. Lawler; W. J. Foley; G. J. Pass; B. M. Eschler (Journal of Comparative Physiology B, 1998)

Vertebrate Herbivory on Eucalyptus—Identification of Specific Feeding Deterrents for Common Ringtail Possums (Pseudocheirus peregrinus) by Bioassay-Guided Fractionation of Eucalyptus ovata Foliage - David M. Pass; William J. Foley; Bruce Bowden (Journal of Chemical Ecology, 1998)

Intraspecific variation in Eucalyptus secondary metabolites determines food intake by folivorous marsupials - I. R. Lawler; W. J. Foley; B. M. Eschler; D. M. Pass; K. Handasyde (Oecologia, 1998)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)